2021
DOI: 10.1016/j.heliyon.2021.e06815
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous septic arthritis of the hip with large abscess formation mimicking soft tissue tumors: A case report

Abstract: Background: Tuberculous septic arthritis is an infection that occurs inside the joint or synovial fluid and joint tissues caused by Mycobacterium tuberculosis. It may show wide variability of clinical symptoms and imaging appearance, ranging from asymptomatic with a normal radiographic examination to severe joint pain along with joint destruction, osteomyelitis, and abscess formation. This article presents radiographic and MR imaging appearance from a case of tuberculous septic arthritis with large abscess for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Tuberculosis of the musculoskeletal system may present with various clinical manifestations that may not closely resemble a typical septic joint [ 5 , 6 ]. While it is important to consider this diagnosis in frail and immunocompromised patients, it is crucial to keep it in the differential diagnosis of healthy patients with no clear predisposing cause, especially when conventional treatment fails to achieve a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuberculosis of the musculoskeletal system may present with various clinical manifestations that may not closely resemble a typical septic joint [ 5 , 6 ]. While it is important to consider this diagnosis in frail and immunocompromised patients, it is crucial to keep it in the differential diagnosis of healthy patients with no clear predisposing cause, especially when conventional treatment fails to achieve a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While some cases such as that reported by Al-Tikrity et al showed more or less the typical form of primary tuberculosis with most of the salient features of tuberculosis of the hip such as pain, limitation of motion, and MRI features suggestive of tuberculosis [ 5 ], other cases such as the one published by Alsaleem et al showed a more insidious course with little or no manifestation of an acutely septic joint and with MRI features that are not specific to tuberculous arthritis [ 12 ]. Other studies reported a more unique presentation of hip tuberculous arthritis that resembled a soft tissue tumor [ 6 ]. This wide spectrum of manifestations presents a unique challenge to orthopedic surgeons and stresses the importance of a high index of suspicion when managing cases of septic arthritis of the hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its slow progression and chronicity cause patients to present with subtle symptoms and signs, resulting in delayed diagnosis. The identification of people who have asymptomatic tuberculosis is a diagnostic challenge[ 8 , 9 ]. From a public health perspective, the concern is whether these people are infectious or not[ 10 ].…”
Section: Discussionmentioning
confidence: 99%